Text and Image in Ricardo Menéndez Salmón’s Novels (2001-2010) (Castilla. Estudios de Literatura, 2012)
Ricardo Menéndez Salmón, a Spanish writer born in Gijón, is the author of eight novels and three books of short stories written over a little more than ten years. He defines himself not as a “book writer” but as a “work writer”, a work in which each story is part of an edifice under permanent construction, a work in progress which the reader, as actor or witness, is an integral part of. It is a piece of writing described by the author as “centripetal”, in which the novels establish a dialogue between one another, where characters reappear and images are repeated, be they mental or verbal constructions produced by the text or conversely graphic images that nurture the writing process. In fact, Ricardo Menéndez Salmón’s works have to be read as a relation between text and image.